Non3 is an essential Drosophila gene required for proper nucleolus assembly - E. N. Andreyeva; A. A. Ogienko; A. A. Yushkova; J. V. Popova; G. A. Pavlova; E. N. Kozhevnikova; A. V. Ivankin; M. Gatti; A. V. Pindyurin (Вавиловский журнал генетики и селекции)
The nucleolus is a dynamic non-membrane-bound nuclear organelle, which plays key roles not only in ribosome biogenesis but also in many other cellular processes. Consistent with its multiple functions, the nucleolus has been implicated in many human diseases, including cancer and degenerative pathologies of the nervous system and heart. Here, we report the characterization of the Drosophila Non3 (Novel nucleolar protein 3) gene, which encodes a protein homologous to the human Brix domain-containing Rpf2 that has been shown to control ribosomal RNA (rRNA) processing. We used imprecise P-element excision to generate four new mutant alleles in the Non3 gene. Complementation and phenotypic analyses showed that these Non3 mutations can be arranged in an allelic series that includes both viable and lethal alleles. The strongest lethal allele (Non3∆600) is a genetically null allele that carries a large deletion of the gene and exhibits early lethality when homozygous. Flies heterozygous for Non3∆600 occasionally exhibit a mild reduction in the bristle size, but develop normally and are fertile. However, heteroallelic combinations of viable Non3 mutations (Non3197, Non3310 and Non3259) display a Minute-like phenotype, consisting in delayed development and short and thin bristles, suggesting that they are defective in ribosome biogenesis. We also demonstrate that the Non3 protein localizes to the nucleolus of larval brain cells and it is required for proper nucleolar localization of Fibrillarin, a protein important for post-translational modification and processing of rRNAs. In summary, we generated a number of genetic and biochemical tools that were exploited for an initial characterization of Non3, and will be instrumental for future functional studies on this gene and its protein product.